FLT3 inhibitors: clinical potential in acute myeloid leukemia - Hospital MA (OncoTargets and Therapy, 2017)
Marie-Anne Hospital,1–3 Alexa S Green,1–3 Thiago T Maciel,4–7 Ivan C Moura,4–7 Anskar Y Leung,8 Didier Bouscary,1–3 Jerome Tamburini1–3 1Département Développement, Reproduction, Cancer, Institut Cochin, Centre National de la Recherche Scientifique (CNRS), Unité Mixte de Recherche (UMR) 8104, Institut National de la Santé et de la Recherche Médicale (INSERM) U1016, 2Faculté de Médecine Sorbonne Paris Cité, Université Paris Descartes, 3Equipe Labellisée Ligue Nationale Contre le Cancer (LNCC), 4INSERM UMR 1163, Laboratory of Cellular and Molecular Mechanisms of Hematological Disorders and Therapeutic Implications, 5Paris Descartes – Sorbonne Paris Cité University, 6CNRS ERL 8254, Imagine Institute, 7Laboratory of Excellence GR-Ex, Paris, France; 8Department of Medicine, Division of Hematology, LKS Faculty of Medicine, The University of Hong Kong, Hong Kong, People’s Republic of China Abstract: Acute myeloid leukemia (AML) is an aggressive hematopoietic malignancy that is cured in as few as 15%–40% of cases. Tremendous improvements in AML prognostication arose from a comprehensive analysis of leukemia cell genomes. Among normal karyotype AML cases, mutations in the FLT3 gene are the ones most commonly detected as having a deleterious prognostic impact. FLT3 is a transmembrane tyrosine kinase receptor, and alterations of the FLT3 gene such as internal tandem duplications (FLT3-ITD) deregulate FLT3 downstream signaling pathways in favor of increased cell proliferation and survival. FLT3 tyrosine kinase inhibitors (TKI) emerged as a new therapeutic option in FLT3-ITD AML, and clinical trials are ongoing with a variety of TKI either alone, combined with chemotherapy, or even as maintenance after allogenic stem cell transplantation. However, a wide range of molecular resistance mechanisms are activated upon TKI therapy, thus limiting their clinical impact. Massive research efforts are now ongoing to develop more efficient FLT3 TKI and/or new therapies targeting these resistance mechanisms to improve the prognosis of FLT3-ITD AML patients in the future. Keywords: AML, FLT3, FLT3-ITD, tyrosine kinase, target therapy, resistance mechanisms